Land conflict, murder, and the rise of “timeless culture” and girl blaming (Samburu, Kenya) - Bilinda Straight (Ateliers d'Anthropologie)
The paper examines youthful practices in the Samburu pastoralist age set system as they evolved into tropes of warrior girlfriends inciting masculine violence. Through a close examination of a well-publicized Kenyan court case surrounding the suspicious death in 1931 of Theodore Powys, a British settler, this paper documents the shaping of a discourse about feminine agency and masculine bravado among the youth that eventuated in harsh state-sponsored collective punishment of a pastoralist Samburu community. Colonial officers and European settlers strategically deployed Samburu youth “culture” in the form of girls’ sexuality and young men’s martial role in the tense, globally significant milieus of land policy and conflict in ways that persist in the twenty-first century. Thus, girls’ sexuality has had political implications that far exceed the lives of individual girls.